Religius Culture dalam Komunitas Sekolah - Siti Majidah (FALASIFA : Jurnal Studi Keislaman, 2018)
ABSTRACT Education contributes greatly to the progress of a nation and is a vehicle for translating constitutional messages and means in building national character (character building). An intelligent society will give a smart nuance of life and will progressively form independence. Schools as one of the educational institutions which are an expansion of the individual's social environment for the development of social relations capabilities and at the same time are new environmental factors that are very challenging or even worrying for him. This is because the factors of the situation or circumstances that affect the learning process in students related to the students themselves, the state of learning, the learning process, teachers who provide lessons, friends learn and get along, as well as learning programs taken. All of them are factors that are closely related to one another. Keywords: Religious Culture, School Community.